2015
DOI: 10.1016/j.rser.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Driving forces of Spain׳s CO2 emissions: A LMDI decomposition approach

Abstract: This paper analyses the role of Renewable Energy Sources (RES) in Spain as a factor to balance the driving force CO2 emissions. To that end, a multi-sectoral analysis based on the Log-Mean Divisia Index Method (LMDI I) was conducted for the 1995-2009 period.Data came from the World Input-Output Database (WIOD) and determined the period under consideration. The paper focuses on the 35 productive sectors included in the WIOD.Major findings show that RES acted in detriment to the drivers of CO2 emissions. This ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(91 citation statements)
references
References 55 publications
5
85
0
1
Order By: Relevance
“…Improvement in the energy efficiency of coal power generation and coal end-use combustion were the primary factors reducing coal consumption. Cansino et al (2015) also used the LMDI I to investigate the driving forces of Spain ‫׳‬ s CO 2 emissions. They found that renewable energy sources acted as a detriment to the drivers of CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Improvement in the energy efficiency of coal power generation and coal end-use combustion were the primary factors reducing coal consumption. Cansino et al (2015) also used the LMDI I to investigate the driving forces of Spain ‫׳‬ s CO 2 emissions. They found that renewable energy sources acted as a detriment to the drivers of CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…For analyzing energy consumption or carbon emissions, SDA is often combined with the input-output model, and the Logarithmic Mean Divisia Index (LMDI) is most prominently used in the IDA (Cansino et al, 2015). Of all the decomposition factors (Table 3), economic development and increased energy consumption are the greatest drivers of carbon emissions, but with the advance of technology, the improvement of energy efficiency will become the most important factor in carbon emissions reductions.…”
Section: Methodsmentioning
confidence: 99%
“…Cansino [74] Spain B20 Dong et al [75] China The CO 2 emission factor of electricity is considered to be zero.…”
Section: B1mentioning
confidence: 99%